Ultrasound features and role of O-RADS classification in the diagnosis of ovarian tumors - Nguyen, Thi Trang; Tran, Van Bao; Dang, Cong Thuan (Tạp chí Y Dược Huế, 2024)
Background: Ovarian tumors are a common condition in women, with 5% - 30% cases being malignant. Clinical symptoms are often nonspecific, causing difficulties in early diagnosis and detection. The O-RADS classification system provides a consistent way to interpret ovarian masses on ultrasound. Aim: The aim of this study is to (1) Describe the ultrasound characteristics of ovarian tumors according to the O-RADS classification. (2) Investigate the signs predicting malignancy in the O-RADS 3, 4, and 5 categories. Materials and Method: This cross-sectional study involved 188 patients who were examined and treated at the Hospital of Hue University of Medicine and Pharmacy, diagnosed with ovarian tumors, from April 2022 to September 2023. Results: 88.8% of ovarian tumors were found to be benign (88.8%), with serous tumors being the most common type in both benign and malignant groups. The distribution of ovarian tumors based on the O-RADS classification was as follows: O-RADS 1 (1.6%), O-RADS 2 (52.1%), O-RADS 3 (22.9%), O-RADS 4 (17.6%), O-RADS 5 (5.9%). Most ovarian tumors were monocystic masses, without solid components (65.4%), with diameters ranging from 50 - 100 mm (58.0%), and had smooth inner borders (79.3%). Papillary growth in inner borders and increased vascularity in Doppler ultrasound (color score: CS = 2 - 4) were found to be predictive factors for malignant ovarian tumors, with adjusted odds ratios (aOR) of 8.5 and 5.5, respectively. Conclusions: Monocystic mass with solid components, multicystic mass with solid components, mass with solid components, irregular inner borders, papillary growth in inner borders, and increased vascularity in Doppler ultrasound (CS = 2 - 4) were identified as predictive factors for malignant ovarian tumors.